(untitled) (Selecciones Matemáticas, 2022)
This paper proposes a simple mathematical model that represents the dynamics of youth play for adolescents from 11 to 18 years. This model is defined by a system of 3 differential equations, which are based on continuous processes. The specification of the classes of our model is based on the group classification of the state of gravity of the problem given in [10]. Then we proceed to find the equilibrium points of the system and its analysis. For our numerical simulation we estimate all the parameters of the model using the research work [6] and we apply the Runge kutta algorithm of order 4. As a result and conclusion it is determined that the problem with the game is endemic among young people. In addition, the prevalence of problems with the game is lower in students aged 15 to 18 than in students aged 11 to 14.